Boosting the registration of land rights in step with the SDG’s - De Zeeuw, C.J. (2020)
This paper identifies the international bodies that can take the lead in working on the institutional, legal and spatial frameworks that are needed for national implementations of the so called fit for purpose land administration. The possible role of World Bank, International Federation of Surveyors (FIG), Joint board of Geospatial Information Societies (JBGIS), Open Geospatial Consortium (OGC), the United Nations Initiative on Global Geospatial Information Management (UN-GGIM) and UN organisations like UN-Habitat and the Food and Agriculture Organisation (FAO), is taken as starting point in this paper. This way, soft components can be taken up to the international level. Also in national and local initiatives this is important.In general the management and implementation of soft components gets less attention than the hard components. In this paper examples are given of national and local initiatives and projects, that act as ‘champions’ in implementation projects.